CO2 geological storage in organic-rich shales of the Irati Formation, Paraná Basin, Brazil - Rocha, Haline de Vasconcellos (2021)
Geological storage of carbon dioxide (CO2) is an efficient and safe long-term storage of this greenhouse-contributing gas. When applied to shales, CO2 injection can enhance shale gas recovery, as well as contribute to CO2 abatement by storing significant amounts of CO2 into its organic porosity and clay content. Shales are classified as unconventional reservoirs and the CO2 storage into this lithology has peculiar characteristics: storage through adsorption into the surface area microporous organic particles and clay minerals. Therefore, understanding shales porosity and associated gas sorption patterns requires a detailed characterization of its organic and mineralogical composition. Parameters such as kerogen quantity, type, and maturity, are controlling factors of organic porosity and of CO2 adsorption and CH4 desorption processes, and consequently drive CO2 storage capacity and hydrocarbon production of organic-rich shales. This research aims to reduce uncertainties regarding CO2 storage in shales. It tests the hypothesis that the Irati Formation at Paraná Basin, can be a feasible target for both CCUS and shale gas production in Brazil, due to its high organic content, large occurrence and proximity to major CO2 emitting sources within the country. Due to heterogeneity of Irati shales - which are attributed to the basins complex thermal history, characterizing its organic and inorganic aspects in a regional scale is a challenging task. In this study, a combined analysis of organic geochemistry, petrology, mineralogy, and gas sorption isotherms is applied to Irati shales characterization. Additionally, the interaction between the organic and inorganic component with CO2 as well as rock-fluid mechanisms in shales are investigated. The result is determining Irati shales storage capacity and overall geological feasibility as a CO2 reservoir and as an unconventional hydrocarbon source-rock. Besides the geological aspects, the thesis brings a multidisciplinary approach towards CO2 storage prospects in Brazil. It presents a general overview of the potential for CCUS in the country and identifies the main legal and regulatory barriers to large-scale CCUS deployment.